LIGAND-BINDING CHARACTERISTICS OF [H-3] DIHYDROALPRENOLOL IN CEREBRAL CORTICAL MEMBRANES OF YOUNG AND OLD SENESCENCE-ACCELERATED MOUSE - SUH, YH; LEE, IS; KIM, SS; CHOI, W; PARK, CW; CHUNG, MH; LIM, JK (ELSEVIER SCIENCE INC, 1993)
1. The values of both K(d) and B(max) of [H-3] dihydroalprenolol binding in the cerebral cortical membranes of old-aged (12 month old) SAM-P/l were not significantly different compared with those of young (2 month old) SAM-P/l. 2. The values of K(i) of metoprolol in the young and old aged SAM were 119 +/- 39.5 nM and 157 +/- 55 nM, respectively. 3. The values of beta1/beta2 ratio of the young and old aged SAM were 1.67 +/- 0.15 and 1.64 +/- 0.13, respectively. 4. These results suggest that there were no significant changes of binding characteristics of beta1 and beta2 adrenoceptors during aging in the cerebral cortex of SAM.